The Effectiveness of Depleted Uranium on Penetrating Ammunition and Its Impact on Environment: a Journal Review - Al Hafiiz, Imam Mukhlis; Widiastuti, Pertiwi; Hirawan, Agung; Cahyaputri, Olivia Thresnayu; Yunika, Syalom; Al-Majid, Muhammad Iqbal; Meireni, Mutia (MUNISI: Military Mathematics and Natural Sciences, 2025)
Nuclear technology has significantly impacted the military, especially in weaponry. Depleted Uranium (DU), a byproduct of uranium purification rich in U-238 with low radiation levels, is notably used in ammunition due to its high density. This study investigates DU's effectiveness as ammunition material compared to tungsten-based alternatives. U.S. Army report on testing involved firing DU at a 150 mm steel plate, demonstrating DU's superior penetration capabilities, with an impulse pressure of 4.6 GPa, unlike tungsten, which tended to ricochet. Despite DU's effectiveness, its use is controversial due to its radioactive properties, though less potent than natural uranium. The International Atomic Energy Agency (IAEA) has found no harmful radioactive activity in DU usage areas, suggesting minimal environmental impact. However, the chemical toxicity of DU poses significant health risks, especially when fragments are inhaled or ingested.